Effects of anaemia development during pregnancy on maternal psychological health - Moon Young Kim; Dong Wook Kwak; Seokyung Kim; Su Young Lee; Hee Jin Park; You Jung Han; Jin Hoon Chung; Ji Hyae Lim; Hyun Mee Ryu (BMJ Mental Health)
Background Anaemia during pregnancy is associated with maternal depressive symptoms during pregnancy and the postpartum period. However, the effect of anaemia development during pregnancy on maternal psychological health in non-anaemic women remains unclear.Objective To investigate the effect of anaemia development during pregnancy on maternal psychological health during pregnancy and the postpartum period.Methods This study includes a secondary analysis of data collected prospectively from the Korean Pregnancy Outcome Study. Depression and anxiety were evaluated in each trimester and 4–6 weeks postpartum. The Hospital Anxiety and Depression Scale was used for anxiety and the Edinburgh Postnatal Depression Scale for depression.Findings Among 3310 women with normal haemoglobin concentrations in the first trimester, 270 (8.1%) developed anaemia in the third trimester. Depression during the first trimester and anxiety during the second trimester were significantly more frequent among patients who later developed anaemia in the third trimester than among those who did not. Even after adjusting for confounding factors, anaemia development during pregnancy was significantly associated with increased risks of depression during the first trimester (aOR, 1.45; 95% CI, 1.07 to 1.96; p=0.017) and anxiety during the second trimester (aOR, 1.57; 95% CI, 1.04 to 2.38; p=0.033), respectively.Conclusions and clinical implications Among women who were non-anaemic in the first trimester and developed anaemia by the third trimester, higher risks of maternal depression and anxiety were observed during the first and second trimester, respectively. It suggests that a decrease in haemoglobin concentrations during pregnancy negatively impacts on maternal psychological health.